Lead Highly Available in Soils Centuries after Metallurgical Activities. Issue 6 (1st November 2017) - Mariet, Anne‐Lise; Sarret, Géraldine; Bégeot, Carole; Walter‐Simonnet, Anne‐Véronique; Gimbert, Frédéric
Abstract : Lead (Pb)‐contaminated sites that resulted from past mining and smelting activities still pose toxicological and ecotoxicological issues worldwide. A large body of research has been dedicated to evaluating the contamination and proposing mitigation strategies for recently contaminated sites (from the 19th century until the present). The possible impact of older contaminations has been much less investigated. The present study focuses on soils affected by Pb‐silver mining and smelting activities during the 15th to 18th centuries. A combination of sequential extractions and X‐ray absorption spectroscopy was used to determine the Pb fractionation and speciation in these soils. Despite the long passage of time, Pb was still highly available (1 and 6% of Pb present in the exchangeable fraction and 46 to 71% in the reducible fraction) and mostly present as Pb sorbed on iron (oxyhydr)oxides. Galena (lead sulfide, PbS) was observed in a soil sample from a kitchen garden, suggesting the recent use of smelter slags as soil amendments. This study shows that Pb is still highly available on this site after almost five centuries, probably because of the acidic character of the soil and the soil composition. Core Ideas: Lead persists in bioavailable form several centuries after waste deposition. Lead was mainly sorbed on Fe‐Mn (oxyhydr)oxides. PbS in soil points to the use of slag as a kitchen‐garden amendment.